Encapsulation of fish oil in soybean protein particles by emulsification and spray drying - Di Giorgio, Luciana (2019)
This manuscript reports a systematic study of encapsulation of fish oil into soybean microparticles by emulsification and subsequent spray drying in order to protect it from lipid autoxidation and/or facilitate its handling for incorporation into healthy food products. In particular, the effect of the formulation and the emulsification technique on the physicochemical properties of the resulting emulsions and encapsulates was evaluated. Two emulsifying processes and four protein:oil ratios were analyzed. Soy proteins managed to encapsulate the fish oil, masking its characteristic odor and its oily texture into matrix type microcapsules, as was observed by confocal microscopy. The emulsification process was determinant in the efficiency of drying and encapsulation as well as in the protection exerted on the oil oxidative stability. Although both, emulsifying and drying processes caused certain initial oil oxidation (verified by peroxide and TBA indexes), some of the studied systems showed a good perspective of oxidative stability over time (studied by accelerated rancimat test).